Penentuan Rute Pengiriman pada Distribusi Produk dengan Pendekatan Capacitated Vehicle Routing Problem (CVRP) Menggunakan Algoritma Genetika : Studi Kasus pada UMKM Cuankie HD Barokah Garut - Cahyadi, Ujang; Taptajani, Dedi Sa'dudin; Mustika, Lesti (Institut Teknologi Garut, 2025)
This study aims to optimize the distribution routes at the MSME Cuankie HD Barokah Garut to improve operational efficiency. The MSME faces challenges in distribution management due to limited resources and suboptimal routing. To address this, the study applies the Capacitated Vehicle Routing Problem (CVRP) approach based on the Genetic Algorithm (GA). CVRP is used to consider vehicle capacity in delivery optimization, while GA is employed to determine optimal routes that minimize distance, time, and operational costs.Data were collected through observations and distance measurements using Google Maps. Before optimization, the total distribution distance reached 101.4 km with a travel time of 325 minutes and operational costs of Rp. 518,200. After optimization, the distribution routes became more efficient, with a total distance of 82.3 km, travel time of 277 minutes, and reduced operational costs of Rp. 471,300.The results show that the Genetic Algorithm significantly improved distribution efficiency by reducing travel distance, travel time, and operational costs. The implementation of GA proved effective in optimizing distribution routes for MSMEs with limited resources.